A constitucionalização da solução pacífica de conflitos na ordem jurídica de 1988 - Lucena Filho, Humberto Lima de (2012)
In the Brazilian legal context, conflict resolution is studied and analyzed over a majority jurisdictional view, which is one of the reasons of litigation culture that creates a jurisdictional resolution hopeness. The practical impact of such reality is the loss of quality in the public service of the judicial function, moved, as a rule, by the overcrowdings, slowness of legal procedures and the relegation of peaceful resolution methods to peripheral plan. However, the Federal Constitution of 1988, following the Ordinary Law constitutionalization phenomenon provides specific guidance about the values towards the litigation resolution. The study, therefore, aims to approach the constitutionalization of conflict resolution in order to identify, through scientific and spiritual interpretation in conjunction with the systematic paradigm, what are these values, as well as operation and legal representation and practice of these measurements. In this sense, the thesis is to study the initial point of the analysis of conflict theories and explanations about the culture of litigation matched with concepts of creation and interpretation, constitutionalization, access to justice and social pacification public policies. It is used for this purpose, the logical-deductive method with the aid of the dialectic immanent in Law